Pod znakiem serca. „Ja” czujące późnej nowoczesności (Leśmian, Joyce, Derrida, Nancy) - Aldona Kopkiewicz (Przestrzenie Teorii, 2016)
In this article I try to show the changing paradigm of romantic expressionism in late modernity. I concentrate on the category of text, which I describe using literature: Bolesław Leśmian’s tale The Adventures of Sindbad the Sailor and a fragment of James Joyce’s Ulysses, as well as theoretical discourses by Jacques Derrida and Jean-Luc Nancy. I am interested first and foremost in the problem of the arbitrary nature of the bond between heart and word, affect and language. I find this problem to be the core of the possibility of thinking about literary creativity, especially its inventive, poetical potention. I try to explain how affect and language meet in the category of textuality and how modern subjectivity can cope with its basic conflict, which lies in the demand of opening and closing itself to the affective experience of otherness.